Integration of Technology and Innovation in Islamic Religious Education Learning Models in the Digital Era: A Systematic Literature Review - Ahmad Sa'roni; Rusdin Rusdin; Iis Arifudin; Nuraini Nuraini (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Islamic Religious Education (PAI) faces significant challenges in adapting to the digital era, particularly following the post-COVID-19 shift from face-to-face to technology-mediated learning. Existing studies tend to examine digital platforms or models in isolation, without evaluating whether technology genuinely reinforces pedagogical quality or undermines Islamic character education values. This study aims to systematically synthesize and critically analyze the effectiveness of digital learning model innovations in PAI, focusing on three dimensions: (1) innovative pedagogical models; (2) educator competency (TPACK) and digital literacy; and (3) infrastructure equity and learning inclusivity. A Systematic Literature Review (SLR) using the PRISMA protocol was employed, reviewing 16 empirical articles from the Scopus database (2018–2026). Findings indicate that technology integration represents a fundamental pedagogical transformation, not mere digitization. Blended learning, flipped classrooms, and digital tools (LMS, AR, PDF Hyperlinks) have been proven to improve learning outcomes and student engagement. However, effectiveness is hampered by low TPACK mastery, urban-rural infrastructure disparities, and inadequate academic supervision. Technological innovation in PAI will only be meaningful when accompanied by holistic teacher capacity development, continuous managerial support, and inclusive infrastructure policies that bridge the digital divide